Synthesis of novel esters of mefenamic acid with pronounced anti-nociceptive effects and a proposed activity on GABA, opioid and glutamate receptors - Ayoub, Rami; Jarrar, Qais Bashir; Ali, Dalia; Moshawih, Said; Jarrar, Qais Bashir; Hakim, Muhammad Nazrul; Zakaria, Zainul Amiruddin (Elsevier BV, 2021)
Background: Mefenamic acid (MFA), a commonly prescribed non-steroidal anti-inflammatory drug (NSAID), possesses a greater risk of dose-related central nervous system (CNS) toxicity than other NSAIDs. In this study, α-tocopherol and α-tocopherol acetate were selected as prodrug moieties for MFA in an attempt to reduce the CNS toxicity and enhance the therapeutic efficacy. Method: α-tocopherol monoester of MFA (TMMA) and α-tocopherol di-ester of MFA (TDMA) were synthesized by esterification reaction and were subjected to various in vivo characterizations. Results: Masking of the carboxylate group of MFA with the proposed pro-moieties significantly (p<0.05) delayed the onset of tonic-clonic seizure in mice. Besides, the intraperitoneal administration of TMMA and TDMA in mice produced significantly (p<0.05) stronger anti-inflammatory effects in the carrageenan-induced paw edema test and greater anti-nociceptive effect in the acetic acid-induced writhing test than MFA at an equimolar dose of 20 mg/kg. Treatment with TMMA and TDMA caused a significant (p<0.05) inhibition of pain at 1st and 2nd phases of formalin-induced licking test in mice, whereas treatment with MFA inhibited the 2nd phase only. Pretreatment with naloxone and flumazenil significantly (p<0.05) reversed the anti-nociceptive effect of MFA, TMMA and TDMA in the acetic acid-induced writhing test. In addition, treatment with TMMA and TDMA caused significantly (p<0.05) a higher inhibition of pain in the glutamate-induced licking response in mice than MFA. Conclusion: Masking the carboxylate moiety of MFA by α-tocopherol and α-tocopherol acetate has a great potential for reducing CNS toxicity, enhancing the therapeutic efficacy and altering the mode of anti-nociceptive action.